The selection advantages associated with advanced biological maturation vary according to playing position in national-level youth soccer - Sweeney, Liam; Cummin, Sean; MacNamara, Áine; Horan, Dan (Biology of Sport, 2023)
This study investigated the extent to which biological maturation selection biases existed according to playing position in national-level youth soccer. A total of 159 players from the U13 to U16 age groups in the Football Association of Ireland’s national talent pathway and international representative squads had their relative biological maturity status assessed using the Khamis-Roche method for the percentage of predicted adult height at the time of observation. Players were categorised as goalkeeper (GK), central defender (CD), full-back (FB), centre defensive midfielder (CDM), centre midfielder (CM), centre attacking midfielder (CAM), wide midfielder (WM) or centre forward (CF). A series of one-sampled means t-tests were used to examine the degree to which biological maturation selection biases existed across playing positions. A non-parametric Kruskal-Wallis test was used to evaluate inter-positional differences. A small to very large selection bias in favour of early maturing players existed for GK (D = 0.7), CD (D = 1.65), FB (D = 0.49), CM (D = 0.62), WM (D = 0.78), and CF (D = 0.76) (p < 0.05). Maturational selection biases did not exist for CDM or CAM. Moreover, CD were significantly more advanced in maturation compared to FB, CDM and CAM (p < 0.05). This study supports the contention that maturation selection biases exist in youth soccer, but the magnitude of this bias is highly dependent upon playing position. The very strong maturity selection biases at the national level evidenced in this investigation highlight the need for Football Associations to explore strategies, such as futures programmes, to help to retain talented, yet late maturing athletes.